Impact of COVID-19 on healthcare-associated infections in Canadian acute-care hospitals: Interrupted time series (2018-2021) - Anada Silva; Jessica Bartoszko; Joëlle Caye; Kelly Baekyung Choi; Robyn Mitchell; Linda Pelude; Jeannette Comeau; Susy Hota; Jennie Johnstone; Kevin Katz; Stephanie Smith; Kathryn Suh; et al. (Cambridge University Press, 2023)
Background: Data regarding the effects of the SARS-COV-2 (COVID-19) pandemic on healthcare-associated infections (HAIs) in Canadian acute-care hospitals are limited. We examined the impact of the COVID-19 pandemic on HAIs and antimicrobial resistant organisms in hospitals participating in the Canadian Nosocomial Infection Surveillance Program. Methods: We analyzed 13,406 HAIs including adult mixed intensive care unit (ICU) central-line-associated bloodstream infections (CLABSIs), and healthcare-associated (HA) Clostridioides difficile infection (CDI), methicillin-resistant Staphylococcus aureus (MRSA) bloodstream infections (BSI), vancomycin-resistant Enterococcus (VRE) BSI, and carbapenemase-producing Enterobacterales (CPE) infections collected using standardized case definitions and questionnaires from 29-64 hospitals participating in the Canadian Nosocomial Infection Surveillance Program (CNISP) from January 2018 to December 2021. We used a generalized linear mixed model with quasi-Poisson distribution to assess step and slope changes in monthly HAI rates between the pre-COVID-19 pandemic period (January 1, 2018-February 29, 2020; 26 time points) and the COVID-19 pandemic period (March 1, 2020-December 31, 2021; 22 time points). Results were reported as incidence rate ratios (IRRs) with 95% confidence intervals (CIs) and adjusted for seasonality, hospital clustering, and hospital characteristics of interest. Results: In the CNISP network, 7,352 (55%) HAIs were reported in the prepandemic period and 6,054 (45%) in the pandemic period. Median age was significantly younger during the pandemic period compared to the prepandemic period among patients with HA-CDI, HA-MRSA BSI, and adult mixed ICU CLABSIs, and more than half of cases among all reported HAIs were male (range, 52%-65%). The 30-day all-cause in-hospital mortality rate did not significantly change between the prepandemic and pandemic periods for all reported HAIs and was highest among HA-VRE BSIs (34%). Modeling results indicated that the COVID-19 pandemic was associated with an immediate increase in HA-CDI and adult mixed ICU CLABSI rates whereas HA-MRSA BSI, HA-CPE and HA-VRE BSI rates immediately decreased. However, pandemic status did not have a statistically significant lasting impact on monthly rate trends for all reported HAIs after adjusting for seasonality, clustering, and hospital covariates (Fig. 1 and 2). Adjusted IRRs for all HAIs ranged from 1.00 to 1.01 (95% CI, 0.94-0.99 to 1.01-1.05).